Synthesis and cytotoxicity of new 2-oxo-7-phenyl-2, 3-dihydrothiazolo[4, 5-b]pyridine-5-carboxylic acid amides. (2nd December 2019) - Lozynskyi, Andrii; Zimenkovsky, Borys; Ivasechko, Iryna; Senkiv, Julia; Gzella, Andrzej; Karpenko, Olexandr; Stoika, Rostyslav; Lesyk, Roman
Abstract: The synthesis and anticancer activity evaluation of new thiazolo[4, 5- b ]pyridine-5-carboxylic acid amides is described. The structures of the synthesized compounds were confirmed by spectroscopic data and a single crystal X-ray diffraction analysis for2.4 . The synthesized compounds were screened for their in vitro anticancer activity according to US NCI protocols. The most active 7-(4-fluorophenyl)-2-oxo-2, 3-dihydrothiazolo[4, 5- b ]pyridine-5-carboxylic acid (4-chlorophenyl)amide2.2 and 7-(4-chlorophenyl)-2-oxo-2, 3-dihydrothiazolo[4, 5- b ]pyridine-5-carboxylic acid (4-chlorophenyl)amide2.5 were screened for their cytotoxicity effects on C6 Rat glioma cells and U373 Human glioblastoma astrocytoma cells which revealed promising results comparable to temozolamide as reference control according MTT assay data. GRAPHICAL ABSTRACT: